Distribution and mitochondrial DNA tracing of the invasive Argentine ants (Linepithema humile) in South Korea. Issue 3 (18th January 2021) - Park, Sang‐Hyun; Ha, Young‐Ho; Kim, Dong Eon; Kim, Chang‐Jun; Choi, Moon Bo
Abstract: Argentine ants ( Linepithema humile ) are one of the world's most invasive species and were first reported in South Korea, near Busan Port in 2019. The distribution of their initial spread was investigated here from April to July 2020. In the invasion area, numerous nests and individuals were identified, indicating that they had settled and successfully invaded the habitat. To track the invasion of the Argentine ants we conducted haplotype analysis using COI, COII, and Cytb sequences of their mitochondrial DNA. The invasive ants had the same mitochondrial haplotype (H3) as Argentine ants from America (Chile, Ecuador, Bermuda) and East Asia (Japan). When comparing the import trade volumes at Busan port with the Argentine ant haplotypes from other countries, it was determined that the invasive ants may have originated from the United States or Japan. Numerous ecological and economic impacts due to their invasion and spread in other countries has previously been reported. Therefore, prompt control measures for the Argentine ants found at Busan port, at this relatively early stage of settlement, is required.